(untitled) (Research, Society and Development, 2025)
Anaerobic infections account for most head and neck diseases and their etiology is mixed. Although their etiological agents generally present low virulence, their populations are high and, in special cases, they can lead to the development of sepsis and infections that can compromise the patient. Metronidazole is considered the antianaerobic chemotherapy agent par excellence, but its clinical use has been extended for more than sixty years, so the resistance to this drug can limit its use. The objective of this study was to discuss the mechanism of action of metronidazole and the impact of resistance to nitroimidazoles, to illustrate the aspects capable of conditioning its clinical use. Through a review of the literature, it was found that the inhibitory action of this drug depends on the reduction of its nitro group, which allows it to interact with microbial DNA, fragmenting it. On the other hand, resistance to this agent can be natural or acquired, when it arises as a consequence of mutations or transfer of resistance genes. It is evident that most anaerobic Gram-negative oral microorganisms are susceptible to nitroimidazoles, whereas anaerobic Gram-positive microorganisms present varied susceptibility and facultative anaerobes and aerobes are, a priori, resistant.